Influence of sperm DNA fragmentation on the clinical outcome of in vitro fertilization-embryo transfer (IVF-ET) - Zhu, Chunhui; Chen, Fang; Zhang, Shengmin; She, Hong; Ju, Yun; Wen, Xidong; Yang, Chunxia; Sun, Yan; Dong, Naijun; Xue, Tongmin; Liu, Kaifeng; Li, Feng; et al. (Frontiers in Endocrinology, 2022)
Abstract Purpose: To evaluate the effect of elevated sperm DFI on fresh and frozen embryo transfer cycles. Methods: A retrospective study was performed with 549 fresh embryo transfer cycles and 1340 frozen embryo transfer (FET) cycles after in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) from 2016 to 2021. Results: The statistical results of 549 fresh embryo transfer cycles showed that the delivery rate in the normal sperm DFI group (43.9% vs. 27.1%, P=0.014) was significantly higher than that in the abnormal sperm DFI group, and there were no significant differences in the biochemical pregnancy rate (59.0% vs. 50.8%, P=0.232), clinical pregnancy rate (53.1% vs. 40.7%, P=0.072), or miscarriage rate (17.3% vs. 33.3%, P=0.098) between the two groups. The results of 1340 FET cycles showed that the biochemical pregnancy rate (57.9% vs. 45.6%, P=0.006) and clinical pregnancy rate (50.3% vs. 40.7%, P=0.027) in the normal sperm DFI group were significantly higher than those in the abnormal sperm DFI group. The delivery rate (40.9% vs. 33.3%, P=0.074) and miscarriage rate (18.6% vs. 18.0%, P=0.919) were not significantly different between the two groups. Conclusion: The increase in sperm DFI significantly reduces the delivery rate of fresh embryo transfer cycles but has no significant effect on the biochemical pregnancy rate, clinical pregnancy rate or abortion rate.